Endothelial-to-Mesenchymal Transition in Cancer - Clere, Nicolas; Renault, Sarah; Corre, Isabelle (Frontiers in Cell and Developmental Biology, 2020)
Cancer is one of the most important causes of morbidity and mortality worldwide. Tumor cells grow in a complex microenvironment constituted of immune, stromal and vascular cells that supports growth, angiogenesis and metastasis. Endothelial cells are major components of the vascular microenvironment. These cells have been described for their plasticity and potential to transdifferentiate into mesenchymal cells through a process known as endothelial-to mesenchymal transition (EndMT). This complex process is controlled by various factors, by which endothelial cells convert into a phenotype characterized by mesenchymal protein expression and motile, contractile morphology. Initially described in normal heart development, EndMT is now identified in several pathologies, and especially in cancer. In this review, we highlight the process of EndMT in the context of cancer and we discuss it as an important adaptive process of the tumor microenvironment that favors tumor growth and dissemination but also resistance to treatment. Thus, we underline targeting of EndMT as a potential therapeutic strategy.